Cognitive Structure Determination of Prospective Science Teacher via Word Association Test - Yilmaz, Ecir (Asian Journal of Education and Training, 2019)
This present study aims to determine the prospective science teachers’ cognitive structure about the domain of buffer solution with word-association test. The research was conducted in the spring semester of the academic year of 2018-2019 with a sample of 71 prospective science teachers in the department of science teaching program at a state university in central Anatolian region in Turkey. To be able map the structures, response frequencies were used. Nine of the 71 prospective science teachers are male and the rests are female. This is a qualitative descriptive study. The word-association test contains eight stimulus words to collect data about prospective science teachers’ cognitive structure for the domain of buffer solution. The opinions of four instructors who has already taught chemistry III (analytical chemistry in content) course to the prospective science teachers were obtained for the appropriateness of the stimulus words used in the present study. The gained data was analyzed by using response frequency map method. The obtained findings have been discussed on the base of the related studies and some suggestions have been made.